Cognitive existential couple therapy (CECT) in men and partners facing localised prostate cancer: a randomised controlled trial. (April 2015) - Couper, Jeremy; Collins, Anna; Bloch, Sidney; Street, Annette; Duchesne, Gillian; Jones, Tessa; Olver, James; Love, Anthony
Abstract : Objectives: To assess the efficacy of cognitive existential couple therapy (CECT) for relationship function, coping, cancer distress and mental health in men with localised prostate cancer and in their partners. Patients Subjects and Methods: A randomised controlled trial was conducted with 62 couples randomly assigned to the six‐session CECT programme or care as usual. The couple's relationship function (primary outcome), and coping, cancer distress and mental health (secondary outcomes) were evaluated at T0 (baseline), T1 (after treatment) and T2 (9 months from T0). A repeated‐measures analysis of covariance model, which incorporated T0 measurements as a covariate, was used to compare treatment groups at T1 and T2. Results: After CECT, patients reported significantly greater use of adaptive coping ( P = 0.03) and problem‐focused coping ( P = 0.01). These gains were maintained at follow‐up, while relationship cohesion had improved ( P = 0.03), as had relationship function for younger patients ( P = 0.01). Younger partners reported less cancer‐specific distress ( P = 0.008), avoidance ( P = 0.04), intrusive thought ( P = 0.006), and hyperarousal ( P = 0.01). Gains were maintained at follow‐up, while relationship cohesion ( P = 0.007), conflict resolution ( P = 0.01) and relational function ( P = 0.009) all improved. Conclusion: CECT resulted in improved coping for patients and lower cancer‐distress for partners. Maintained over time this manifests as improved relationship function. CECT was acceptable to couples, alleviated long‐term relationship decline, and is therefore suitable as a preventative mental health intervention for couples facing prostate cancer. Given resourcing demands, we recommend dissemination of CECT be targeted at younger couples, as CECT was more acceptable to the younger group, and they derived greater benefit from it.